2018
DOI: 10.18203/2320-1770.ijrcog20182369
|View full text |Cite
|
Sign up to set email alerts
|

Study of awareness of contraception in postnatal women

Abstract: Background: This study was undertaken to know the awareness of contraception in postnatal women in a Government Hospital in Maharashtra.Methods: Authors conducted a prospective study in Department of Obstetrics and Gynecology at Government hospital, Miraj between January 2015 to September 2016. All postnatal patients in this hospital, willing to participate in the study were included in the study after a thorough written informed consent. Patients were given pre decided questions for answering. Answers were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
5
1
Order By: Relevance
“…26 This study is differ from Rokade et al 2018 where most common reason for not using contraception was wanted to conceive (46%) followed by fear of side effects (24.7%),lack of information (23.4%),decision of family (3.9%),husband staying away (2.1%). 11 In present study, significant association (p<0.05) found between education and KAB score. We found that educational status of the women and per capita income were significant predictor of higher level of knowledge about contraception.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…26 This study is differ from Rokade et al 2018 where most common reason for not using contraception was wanted to conceive (46%) followed by fear of side effects (24.7%),lack of information (23.4%),decision of family (3.9%),husband staying away (2.1%). 11 In present study, significant association (p<0.05) found between education and KAB score. We found that educational status of the women and per capita income were significant predictor of higher level of knowledge about contraception.…”
Section: Resultssupporting
confidence: 54%
“…The mean age group in present study population was 24.6 years. This study is contrast to Gaikwad et al 2017, Rokade et al 2018 and Sharma et al 2015 in which majority of women were respectively in age group of 25-34 years, 26-30 years (mean age was 23 years), 16-47 years (mean age was 28.45.3 years) [10][11][12]. This may be because contraceptive use varies with age, usually reaching peak around 21-25 years and then declining.…”
contrasting
confidence: 69%
See 3 more Smart Citations